A Development Framework to Determine the Applicability of a Dry Port to Fremantle Port Supply Chains: a Case Study - Crockford, Gary Ian (Curtin University, 2022)
Fremantle Ports’ landside container transport has environmental and social impacts and, through congestion, reduces the efficiency of its hinterland links. Incorporating dry ports into supply chains can reduce these impacts and increase seaport capacity and effective life. Using dry port characteristics, common criteria and development theory with a Fremantle Ports case study and user survey, a dry port development framework is established and validated. The framework demonstrates a dry port's role in Fremantle Ports operations.